Cytopathology and occurrence of round cell tumours in dogs in and around Meerut, Uttar Pradesh - Singh, Gulshan Kumar; John, Jeny Kalluvila; Sarkar, Tarun Kumar; Jithin, Mullakkalparambil Velayudhan; Jaiswal, Vikas; Chandra, Naresh (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Round cell tumors represent the most prevalent skin tumors observed in dogs, predominantly manifesting in the skin or subcutaneous regions, although occurrences can be identified in various other locations. Dogs serve as valuable models for investigating the pathogenesis of cancers in humans due to the analogous behavior of tumors. Among the five types of round cell tumors in dogs are mast cell tumors (MCT), lymphoma, plasma cell tumors, histiocytoma, and transmissible venereal tumors (TVT). This study focuses on the occurrence and cytopathology of round cell tumors in Meerut district, Uttar Pradesh, spanning the period from 2018 to 2022. A total of 147 samples were gathered from skin nodules, tumors, skin lesions, penile growth and the vagina. Notably, 95 samples originated from vaginal specimens, 24 from nodular skin swellings,7 samples were from penile growths, 5 from lymph nodes, and the remaining from various skin lesions. The analysis of these samples revealed 4 cases of lymphoma, 3 cases of mast cell tumors, and 28 cases of TVT. In lymphoma, one case was identified as cutaneous lymphoma, while three cases were associated with lymph nodes. Cutaneous lymphoma exhibited numerous small and medium-sized lymphocytes, some presenting a hand-mirror appearance, accompanied by a significant number of red blood cells and a few neutrophils. Lymph node samples exhibited a substantial presence of large-sized and medium-sized lymphocytes, along with lymphoglandular bodies. TVT emerged as the most prevalent round cell tumor in this study, observed in both genital and extragenital forms. Extragenital TVT predominantly affected the skin. In mast cell tumors, cells demonstrated round characteristics, with a notable granules in the cytoplasm and infiltration of eosinophils. Minimal anisocytosis and anisokaryosis, coupled with a high nuclear-to-cytoplasmic ratio, were evident in these tumors.